Systematic review and meta-analysis of enhanced recovery programmes in gastric cancer surgery. (July 2015) - Beamish, Andrew James; Chan, David Sheng Yi; Blake, Paul A.; Karran, Alexandra; Lewis, Wyn Griffith
Abstract: This systematic review and meta-analysis was performed to determine the influence of enhanced recovery programmes (ERPs) on outcomes after gastric cancer surgery. Medline, Embase, the Cochrane library andClinicalTrials.gov were searched for studies on outcomes of gastrectomy in enhanced recovery or fast-track programmes. The primary outcome measure was post-operative duration of hospital stay (LOHS), and secondary outcome measures were selected based inclusion in two or more studies. Statistical analysis was performed using standardized mean difference (SMD) and odds ratio (OR) as the summary statistics. Fourteen studies, totalling 1676 patients with gastric cancer were analysed, including nine randomized trials. LOHS was significantly shorter after ERP when compared with control patients (CON, SMD −1.10, 95% confidence interval −1.56 to −0.65, p < 0.001), but with significant heterogeneity between studies (I 2 = 93%, p < 0.001). ERP was also associated with reduced serum inflammatory response (CRP: SMD −0.68 (−1.16 to −0.19), p = 0.007; IL-6: SMD −0.62 (−0.94 to −0.29), p < 0.001), less weight loss (SMD −0.79 (−1.11 to −0.46), p < 0.001), and lower cost (SMD −1.02 (−1.59 to −0.45), p < 0.001), as well as a trend toward shorter duration of intravenous infusion (SMD −2.70 (−5.35 to −0.05), p = 0.05). Inclusion in an ERP was not associated with increased post-operative morbidity (OR 0.83 (0.65 to 1.06), p = 0.13) or hospital readmission (OR 1.67 (0.88 to 3.19), p = 0.12). From this review the authors concluded that multimodal, standardized perioperative gastrectomy care appears feasible, safe and cost effective. Highlights: The most comprehensive and up-to-date meta-analysis comparing ERPs with conventional gastric cancer surgery treatment. LOHS was significantly shorter in ERP patients. Additional benefits includereduced inflammation, weight loss and cost, without increased morbidity/mortality or readmission. ERPs appear safe, feasible and cost-effective in gastrectomy.